SINDROME METABOLIK PADA ORANG DEWASA GEMUK DI WILAYAH BOGOR - Muherdiyatiningsih Muherdiyatiningsih; Fitrah Ernawati; Rustan Effendi; Susilowati Herman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
Metabolic Syndrome Among Obese Adults In Bogor Area.Background: Metabolic syndrome, also known by the insulin resistance syndrome, is a common metabolic disorder that result from the increasing prevalence of obesity. Little information exists on the prevalence of the metabolic syndrome in Indonesia.Objectives: To find out proportion of metabolic syndrome and factors related to-demographic and potentially modifiable lifestyle factors among obese adults in Bogor area.Methods: Metabolic syndrome, as defined by the US National Cholesterol Education Program - Adult Treatment Panel III (NCEP-ATP III) criteria, were evaluated in two districts in Bogor sample of 221 overweight and obese (Body Mass Index > 25 kg/m2) women and men aged 30-55 years who participated in the correlational study on Profile of the Body and Serum Fats Distribution and Physical Activity among adults with BMI > 25 kg/m2 in Bogor rural and urban, 2003.Results: The metabolic syndrome was present in 36.2 percent of 221 men and women aged 31-55 years which have BMI > 25 kg/m2. The syndrome was significantly more frequent in men (44%) than women (28.6%) [P=0.017]. The syndrome was present in 92.3, 62.9, and 40.3 percent of central obesity, low HDL-cholesterol, and high triglycerides level, respectively. Age of the subject > 44 years, the men factor, physical inactivity, and Waist-Hip Ratio (WHR) > 0.93 were the significantly risk factors associated with increased odds of the metabolic syndrome.Conclusions: The metabolic syndrome was present in high prevalence of the two subdistricts in Bogor obese adults. However, upon thinking about the syndrome was associated with several modifiable lifestyle factors (physical activity, WHR), there was an opportunity to reduce proportion of metabolic syndrome by increasing physical activity that also make lower WHR.Keywords: metabolic syndrome, adulthood obesity, NCEP-ATP III, risk factors